Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=x+\left\{\left(x+5\right)-\left[\left(5-x\right)-\left(-x-3\right)\right]\right\}\)
\(=x+\left\{\left(x+5\right)-\left[5-x+x+3\right]\right\}\)
\(=x+\left\{\left(x+5\right)-\left(5+3\right)\right\}\)
\(=x+\left\{\left(x+5\right)-8\right\}\)
\(=x+\left\{x+5-8\right\}=x+\left\{x-3\right\}\)
\(=x+x-3=2x-3\)
\(B=x.\left\{\left[-x-2-\left[x+\left(3-x\right)-\left(x+3\right)\right]\right]\right\}\)
\(=x.\left\{\left[-x-2-\left[x+3x-x-x-3\right]\right]\right\}\)
\(=x\left\{\left[-x-2-\left(4x-2x-3\right)\right]\right\}\)
\(=x\left\{\left[-x-2-\left(2x-3\right)\right]\right\}\)
\(=x\left\{-x-2-2x+3\right\}\)
\(=x\left(1-3x\right)=x-3x^2\)
a, A=31+32+33+...+32006
3A=32+33+...+32006+32007
3A-A=(32+33+...+32006+32007)-(31+32+33+...+32006)
2A=32007-3
A=(32007-3)/2
b, 2A=32007-3
2A+3=32007
Hay 3x=32007
=>x=2007
a) Bạn Nguyễn Lê Phước Thịnh giải rồi nha bạn :)
b) (-9-x+2)+9
=-9-x+2+9
=-9+(-x)+2+9
=(-x)+(-9+2+9)
=(-x)+2
c) 66-(12-x)+(12-66)
=66-12+x+12-66
=x
d) 15-(15-x+93)+93
=15-15+x-93+93
=x